2004
DOI: 10.1074/jbc.m313828200
|View full text |Cite
|
Sign up to set email alerts
|

Glial Lipoproteins Stimulate Axon Growth of Central Nervous System Neurons in Compartmented Cultures

Abstract: The role of lipoproteins secreted by cortical glial cells in axon growth of central nervous system (CNS) neurons was investigated. We first established compartmented cultures of CNS neurons (retinal ganglion cells). Addition of glial cell-conditioned medium (GCM) to distal axons increased the rate of axon extension by ϳ50%. Inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase in glial cells diminished the secretion of cholesterol and apolipoprotein E, and prevented the growth stimulatory effect of GCM. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 66 publications
5
134
1
1
Order By: Relevance
“…Cholesterol and glial-conditioned medium have a well-documented role in promoting axonal outgrowth in vitro under physiological conditions. Glial-derived lipoproteins containing cholesterol stimulate axon growth 27 and transcription of genes involved in dendrite and synapse development 28 in primary rat retinal ganglion cells; their co-culture with glial cells enhances synaptic activity and neurite outgrowth and branching in Purkinje neurons, 29 and cholesterol deficiency inhibits dendrite outgrowth in primary cortical and hippocampal neurons. 30 Impairments in astrocytic function are increasingly recognized as a culprit in neuronal dysfunction in neurodegenerative diseases, 31 such as amyotrophic lateral sclerosis, 32 Rett's syndrome, 33,34 lysosomal disorders, 35 Alzheimer's disease, 36 and HD.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol and glial-conditioned medium have a well-documented role in promoting axonal outgrowth in vitro under physiological conditions. Glial-derived lipoproteins containing cholesterol stimulate axon growth 27 and transcription of genes involved in dendrite and synapse development 28 in primary rat retinal ganglion cells; their co-culture with glial cells enhances synaptic activity and neurite outgrowth and branching in Purkinje neurons, 29 and cholesterol deficiency inhibits dendrite outgrowth in primary cortical and hippocampal neurons. 30 Impairments in astrocytic function are increasingly recognized as a culprit in neuronal dysfunction in neurodegenerative diseases, 31 such as amyotrophic lateral sclerosis, 32 Rett's syndrome, 33,34 lysosomal disorders, 35 Alzheimer's disease, 36 and HD.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Glial cells serve an important role in the supply of adequate amounts of cholesterol. In addition to its close link to the myelination process, gliaderived cholesterol has recently been demonstrated as essential for synaptogenesis, [18][19][20] acting as a glial growth factor. These data point at lipogenesis and myelin synthesis as interesting etiological candidate targets in schizophrenia, especially in light of the proposed neurodevelopmental disturbances in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Compartmented Culture of RGCs-RGCs in compartmented cultures were prepared as described previously (12,20). Distal axons and cell bodies/dendrites/proximal axons of the primary neurons can be separately maintained with different media in compartmented cultures.…”
Section: Intracellular Ca 2ϩmentioning
confidence: 99%
“…This response of glia to nerve injury has been suggested to provide support for the repair of neurons by supplying materials for the cells. We have reported that gliaderived E-LPs promote axon extension of RGCs mediated by receptor(s) of the low density lipoprotein (LDL) receptor family after axon injury (12). One multifunctional endocytotic and signaling receptor of this family is the LDL receptor-related protein 1 (LRP1).…”
mentioning
confidence: 99%